Design and optimization of a novel composite bionic flow field structure using three-dimensional multiphase computational fluid dynamic method for proton exchange membrane fuel cell. (1st November 2021) - Xia, Lei; Yu, Zeting; Xu, Guoping; Ji, Shaobo; Sun, Bo
Highlights: A novel leaf vein bionic field (LVFF) is proposed based on the feathered veins of plants. The LVFF is optimized by changing the number of branching channels, and is evaluated by power output, parasitic power, reaction gas distribution and water removal capacity. A bionic streamlined block was designed by studying the forms of dropping water droplets and birds. A novel composite bionic flow field was formed by adding streamline blocks into leaf vein bionic field. Abstract: The flow field structure of proton exchange membrane fuel cell (PEMFC) plays a crucial role in fluid flow, species transport, heat transfer and electrochemical reaction of PEMFC. In this study, an improved leaf vein bionic flow field (LVFF) is designed according to the characteristics of the leaf vein network structure. The flow field structure is optimized with the number of branch channels on one side of the main channel, and a detailed performance study of PEMFC with the LVFF has been conducted by the developed three-dimensional (3-D) multiphase computational fluid dynamic (CFD) model which is verified with the experiment data. It is found that the LVFF has the advantages of lower pressure drop, more uniform reaction gas distribution, and a higher power output compared to the conventional flow field. It is found the LVFF with 10 branch channels (named BC-10) on one side of the main channel has the largest power output, which is increased by 5.894% than the power output of the convention serpentine flow field (CSFF) design. Furthermore, the bionic streamline blocks are placed inside branch channels based on BC-10 configuration to construct a composite bionic flow field (CBFF) by which it seeks the potential to further improve the performance of PEMFC. It is found that the maximum power output of the CBFF is increased by 8.475% than the serpentine flow field's. In addition, the distribution of reaction gas and current density are found more uniform. The novel composite bionic flow field structure is beneficial to the performance improvement and long-term steady operation of PEMFC.